Consumer Reaction to Global Economic Qownturn: Changes in Consumer Purchasing Behaviour in China - Li, Kai (2010)
There are rumors (or facts?) that consumers have changed their consumer behavior during the recent global economic downturn. Reports by major consumer research groups have indicated that consumer behavior has been altered in many markets, such as United States, EU, Japan, South Korea, etc. However, there are currently no any researches about Chinese consumers‟ individual purchasing behavior during the global economic downturn have been undertaken. Therefore, this research is going to fill up the gap to investigate whether or if any, how Chinese consumer‟s individual purchasing behavior has been altered during the current global economic downturn. Due to the limited time length, this research will focus on the changes of individual consumers‟ purchasing behavior on food sector. In light of individual‟s food purchasing behavior, five indicators: purchasing frequency, brand loyalty, retail preference, type of product, and volume of product have been arranged as five research questions to lead the research. In attempting, a qualitative-based research is employed. Four focus-group interviews comprise of civil servants, middle class managers, rural-urban migrant workers, and also blue-collar workers and private entrepreneurs, was conducted in Changchun City, which located in Northeast of China. Results indicate that consumers in China are less likely to alter their individual food purchasing behavior during the current global economic downturn. However, the result might be bothered by three main reasons such as rising CPI in 2008, government‟ efforts-stimulus packages, and geographic issues. On the other hand, despite the insipid result, data shows some trends about Chinese consumer‟s food purchasing behavior: if their income were declining or prices of food increasing sharply, blue-collar and middle class workers are more likely to change their purchasing frequency and type of product; blue-collar workers are more likely to switch to other brands; purchasing channel is the least factor that China‟s consumer to change; rural-urban migrant workers and private entrepreneurs are the two groups of people with a relatively stable food purchasing behavior.